Find the derivative of the function. \[ y=\frac{e^{x}}{5}-7 x+2 x^{2} \] \( y^{\prime}=5 x^{4} e^{x 5}-7+4 x \) Please try again. Apply the Constant Function Rule, the Powers of \( x \) Rule, and the Sum Rule. . Constant Function Rule: If \( f(x)=c \), where \( c \) is a constant, then \( f^{\prime}(x)^{\prime}=0 \). - Powers of \( x \) Rule: If \( f(x)=x^{n} \) then \( f^{\prime}(x)=n x^{n-1} \) - Sum Rule: If \( f(x)=u(x)+v(x) \) then \( f^{\prime}(x)=u^{\prime}(x)+v^{\prime}(x) \).
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To find the derivative of the function \( y = \frac{e^{x}}{5} - 7x + 2x^{2} \), we will use the Constant Function Rule, the Powers of \( x \) Rule, and the Sum Rule. First, we apply the Constant Function Rule to the term \( \frac{e^{x}}{5} \). The derivative is: \[ \frac{1}{5} e^{x} \] Next, we differentiate \( -7x \) using the Powers of \( x \) Rule: \[ -7 \] For the term \( 2x^{2} \), applying the Powers of \( x \) Rule gives: \[ 4x \] Now we combine these results using the Sum Rule: \[ y' = \frac{1}{5} e^{x} - 7 + 4x \] Thus, the derivative of the function is: \[ y' = \frac{1}{5} e^{x} + 4x - 7 \] So the correct answer is: \[ y' = \frac{1}{5} e^{x} + 4x - 7 \]